Raw phones: the domestication of mobile phones amongst young adults in Hooggenoeg, Grahamstown - Schoon, Alette Jeanne (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
This dissertation examines the meanings that young adults give to their mobile phones in the township of Hooggenoeg in Grahamstown in the Eastern Cape. The research was predominantly conducted through individual interviews with nine young adults as well as two small gender-based focus groups. Participant observation as well as a close reading of the popular mobile website Outoilet also contributed to the study. Drawing on Silverstone, Hirsch and Morley's (1992) work into the meanings attributed to the mobile phone through the domestication processes of appropriation, objectification, incorporation and conversion, the study argues for the heterogeneous roles defined for mobile phones as they are integrated into different cultural contexts. The term 'raw phones' in the thesis title refers to a particular cultural understanding of respectability in mainly working-class 'coloured'Â¹ communities in South Africa, as described by Salo (2007) and Ross (2010), in which race, class and gender converge in the construction of the respectable person's opposite "“ a lascivious, almost certainly female, dependent, black and primitive 'raw' Other. The study argues that in Hooggenoeg, the mobile phone becomes part of semantic processes that define both respectability and 'rawness' , thus helping to reproduce social relations in this community along lines of race, class and gender. A major focus of the study is the instant messaging application MXit, and how it assists in the social production of space, by helping to constitute both private and dispersed network spaces of virtual communication, in a setting where social life is otherwise very public, and social networks outside of cyberspace are densely contiguous and localised. In contrast, gossip mobile website Outoilet seems to intensify this contiguous experience of space. My findings contest generalised claims, predominantly from the developed world, which assert that the mobile phone promotes mobility and an individualised society, and show that in particular contexts it may in fact promote immobility and create a collective sociability.
Keywords: Cell phones -- Social aspects -- South Africa -- Grahamstown; Communication -- Sex differences -- South Africa -- Grahamstown; Social media -- South Africa -- Grahamstown; Interpersonal communication -- Technological innovations -- Social aspects -- South Africa -- Grahamstown; Communication and culture -- South Africa -- Grahamstown; Online social networks -- Social aspects -- South Africa -- Grahamstown; Mobile communication systems -- Social aspects -- South Africa -- Grahamstown; Identity (Psychology) in youth; Colored people (South Africa) -- Social life and customs -- South Africa -- Grahamstown Colored people (South Africa) -- Ethnic identity -- South Africa -- Grahamstown